A novel stress-induced martensitic transformation in a single-phase refractory high-entropy alloy. (December 2020) - Wang, Liang; Cao, Tangqing; Liu, Xudong; Wang, Benpeng; Jin, Ke; Liang, Yaojian; Wang, Lu; Wang, Fuchi; Ren, Yang; Liang, Jun; Xue, Yunfei
Abstract: High-entropy alloys (HEAs) provide a new perspective to design metastable alloys with the stress-induced martensitic transformation (SIMT) for overcoming the strength-ductility trade-off. Here, we report a novel SIMT, orthorhombic to hexagonal close-packed martensite, in a single orthorhombic refractory HEA (Ti16 Zr35 Hf35 Ta14 RHEA), showing a good yield strength-ductility matching. The analysis of the elastic distortion energy (∆ E els ) of Ti16 Zr35 Hf35 Ta14 and several other RHEAs reveals that severe lattice distortion is a key factor which causes this SIMT. Combined the "d-electron alloy design" approach with the ∆ E els, the phase configuration and SIMT path in RHEAs can be well predicted. Our work brings new insights between the lattice distortion and SIMT of RHEAs, benefiting the metastable alloy development. Graphical abstract: Image, graphical abstract